Pengembangan Bahan Ajar Digital Flipbook Berpendekatan Kontekstual Untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar - Nayla Habibah; Andriani Kumala Dewi, Ririn; Fatkhiyani , Kiki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of fourth-grade students at SD Negeri 1 Juntiweden, Indramayu Regency, in the 2024/2025 academic year in the subject of Natural and Social Sciences (IPAS), along with the limited ability of teachers to develop interactive and contextually relevant teaching materials, served as the basis for this research. One proposed solution is the development of digital flipbook teaching materials using a contextual approach that connects the subject matter to students’ real-life experiences. This study aims to determine the feasibility of the contextual approach-based digital flipbook teaching materials developed and determine the improvement in students' learning outcomes after using the materials. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The sample consisted of 32 fourth-grade students at SD Negeri 1 Juntiweden. Data were collected through expert validation, response questionnaires, and learning outcome tests. Validation results showed that the digital flipbook teaching materials were highly feasible, as assessed by subject matter experts, media experts, and language experts, all of whom rated them in the "very feasible" category. The N-Gain test results indicated an improvement in students’ learning outcomes, with the average pre-test score rising from 48.13 to 76.56 in the post-test, and an N-Gain score of 0.56 (moderate category). Therefore, it can be concluded that the contextual approach-based digital flipbook teaching materials are effective in improving student learning outcomes in IPAS at SD Negeri 1 Juntiweden, Indramayu Regency, for the 2024/2025 academic year.